2015
DOI: 10.1007/s11904-015-0268-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel Neuroimaging Methods to Understand How HIV Affects the Brain

Abstract: In much of the developed world, the HIV epidemic has largely been controlled by anti-retroviral treatment. Even so, there is growing concern that HIV-infected individuals may be at risk for accelerated brain aging, and a range of cognitive impairments. What promotes or resists these changes is largely unknown. There is also interest in discovering factors that promote resilience to HIV, and combat its adverse effects in children. Here we review recent developments in brain imaging that reveal how the virus aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
0
20
1
Order By: Relevance
“…Despite a growing body of studies, the patterns and spatial distribution of brain injury remains unclear 5 . For example, increased putamen volume was detected in HIV-infected individuals compared to an age- and education-matched HIV-uninfected group 6 , while other studies have reported decreased putamen volume 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite a growing body of studies, the patterns and spatial distribution of brain injury remains unclear 5 . For example, increased putamen volume was detected in HIV-infected individuals compared to an age- and education-matched HIV-uninfected group 6 , while other studies have reported decreased putamen volume 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior neuroimaging studies in adults with HIV have reported that HIV severity was related to reduced global and regional brain volumes in both untreated patients and those treated with cART (Ances et al, 2012; Archibald et al, 2004; Becker et al, 2012, 2011; Cohen et al, 2010b; Heindel et al, 1994; Jernigan et al, 1993; Kallianpur et al, 2013; Stout, 1998; Thompson et al, 2005; Thompson and Jahanshad, 2015). Findings on cortical changes varied but overlapped between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies including neuroimaging combined with cognitive evaluation allow for an in vivo characterization of how HIV and cART may mediate brain development (Thompson and Jahanshad, 2015). In adults, studies of post-mortem tissue and in vivo neuroimaging combined with cognitive testing have revealed atrophy in cortical and subcortical structures that is related to HIV severity and cognitive performance (Ances et al, 2012; Archibald et al, 2004; Becker et al, 2012, 2011; Cohen et al, 2010a; Heindel et al, 1994; Jernigan et al, 1993; Kallianpur et al, 2013; Stout, 1998; Thompson et al, 2005; Thompson and Jahanshad, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, neuroimaging has contributed significantly to defining the neurologic manifestations of HIV-1 infection since the onset of the AIDS pandemic; neuroimaging remains invaluable in distinguishing lesions due to opportunistic CNS disease. Computerized tomography (CT) and magnetic resonance imaging (MRI) were utilized early in the HIV epidemic to detect encephalitis and damage to white matter (WM) (Thompson and Jahanshad, 2015). These earlier studies found that WM and caudate loss was accompanied with a larger CNS space in HIV patients (Stout et al , 1998).…”
Section: Neuroimaging Biomarkers For Hiv/neuroaidsmentioning
confidence: 99%